2021
DOI: 10.1108/ijbm-01-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Greening crowdfunding campaigns: an investigation of message framing and effective communication strategies for funding success

Abstract: PurposeRecognising the growing importance of environmental and sustainable activities and the role of communication strategies in soliciting their financing, this work investigates the influence of message framing, green emphasis and quantitative information on the probability of green crowdfunding campaigns' success.Design/methodology/approachThis analysis is based on crowdfunding campaigns published between 2015 and 2020 on the Indiegogo platform in the category “Community projects – Environment”. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…Among the five primary factors contributing to the crowdfunding success of green products, "green diversified context" was the most influential, agreeing with the results of previous studies because "context"-related factors were found to be crucial to crowd-funding success socially [32,78,79,83,[86][87][88][89], environmentally [32,80], politically [82], and economically [82]. Further, the value of a green-diversified context perceived by funders also echoes the findings of previous studies in terms of the general consent regarding the importance of environmental, economic, and social impacts to sustainability [58,66].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the five primary factors contributing to the crowdfunding success of green products, "green diversified context" was the most influential, agreeing with the results of previous studies because "context"-related factors were found to be crucial to crowd-funding success socially [32,78,79,83,[86][87][88][89], environmentally [32,80], politically [82], and economically [82]. Further, the value of a green-diversified context perceived by funders also echoes the findings of previous studies in terms of the general consent regarding the importance of environmental, economic, and social impacts to sustainability [58,66].…”
Section: Discussionsupporting
confidence: 90%
“…Cosma et al [79] concluded that the variety of partners in a platform's network influences crowdfunding success. Rossolini et al [80] emphasized three communication strategies (message framing, green emphasis, and quantitative goals) essential for green product crowdfunding, and dos Santos Felipe et al [81] regarded exposure times, the number of supporters, and the higher volume of rewards as three elements based on practical aspects. Given the importance of the four mentioned factors (green product design, manufacturing, marketing, and the green diversified context) in the product life cycle for green products, as well as their value to sustainability, this study considers the following hypothesis.…”
Section: Factors Affecting Crowdfunding Successmentioning
confidence: 99%
“…Third, crowdfunding ecosystems are complex, collective and collaborative networks in which resources are integral to project success. Scholars have examined backer- (Bagheri et al, 2019;Zhang and Chen, 2019;Zhang et al, 2019), entrepreneur-(Buttic e andRovelli, 2020;Kim and Hall, 2020) and project-related characteristics and presentation design (Moradi and Dass, 2019;Robiady et al, 2021;Rossolini et al, 2021) in successful crowdfunding projects. However, all such works adopted a homological perspective.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…However, information asymmetry can occur due to a lack of backer experience and expertise (Moradi and Badrinarayanan, 2021), insufficient information regarding project and entrepreneur characteristics (Ryu and Kim, 2018) and entrepreneurs' reluctance to disclose detailed project information in an effort to protect their innovations (Kang et al. , 2016; Rossolini et al. , 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…focusing on the advantages of climate mitigation strategies) or negative (e.g. focusing on the threats of climate change) (Maehle et al., 2021; Rossolini et al., 2021). Another strategy used by some social enterprises is to instrumentalize philanthropic investors by encouraging them to share their personal stories to motivate potential investors (Maclean et al., 2013).…”
Section: Descriptive Findings: Mapping a Diversified Landscapementioning
confidence: 99%